Intervarsity ingenuity: English language competitions with UniKL MSI / Noor Azli Affendy Lee, Muhammad Aiman Abdul Halim and Nur Ilianis Adnan - Affendy Lee, Noor Azli; Abdul Halim, Muhammad Aiman; Adnan, Nur Ilianis (Academy of Language Studies, 2022)
The ‘Intervarsity Language Match’ was the first joint event initiated by the English Language Club of UiTM Cawangan Pulau Pinang and Universiti Kuala Lumpur - Malaysian Spanish Institute (UniKL MSI). With the theme ‘Mind Your English’, the open friendly competition was held to encourage and develop students’ creativity and to showcase talents from both universities in relation to the English language. At the same time, it was organised to encourage networking opportunities among students to further strengthen the relationship between the two nearby institutions. In addition, students got to have fun in a post-pandemic physical setting after having been confined to their respective learning spaces due to the COVID-19 pandemic. Students from both universities were given the opportunity to participate in four competitions for free,